ALAT PENCATAT TEMPERATUR OTOMATIS MENGGUNAKAN TERMOKOPEL BERBASIS MIKROKONTROLER AT89S51 - Wendri, Nyoman; Supardi, I Wayan; Suarbawa, K N; Yuliantini, Ni Made (BULETIN FISIKA, 2012)
An automatic temperature reader has been made by using a thermocouple based on microcontroller AT89S51. The automatic temperature works in range 0°C-66°C which has 6,07% linierity. The sensors of thermocouple works by detect changes of heat, producing in difference of voltage which then will be read by microcontroller AT89S51. The detection data given, will then be send into a PC for it to be further analyzed and finally-shown. The program used for this is Visual Basic 6. The relationship of voltage and temperature is interpolasi polynomial.